Zona Integritas dan Pengendalian Gratifikasi dalam Peralihan Hak Atas Tanah pada Kantor Pertanahan di Indonesia - Siti Chadijah; Dwi Kusumo Wardhani; Abdul Hayy Nasution (Program Studi Hukum Universitas Pamulang, 2021)
The purpose of this study is to describe and analyze the problems of public services in the land office and to analyze the efforts made to control gratification in the Land Office. The research method used is Socio Legal, the effect of legal rules on certain social problems, in this case analyzing the legal rules of public services and the eradication of corruption associated with the implementation of public services at land offices in Indonesia with a case-based approach.The results in this study, on the one hand, found a form of problematic public services at the land office, namely the massive gratification carried out by officials / ASN. However, on the other hand, efforts have been made to control gratuities, including the Head of BPN regulation Number 15 of 2013 concerning Gratuity Control, which still has weaknesses in its application, so that further efforts are needed to create an Integrity Zone in land offices in Indonesia.